Representative Relation And Expression Of The Semantic Methodological Task In The Number Category (Texas Journal of Multidisciplinary Studies, 2023)
In the article, the ideas about the opposite meaning of the number category formed with the help of the -lar affix are analyzed through linguistic evidence.